Anti-quorum sensing and antibiofilm activities of Blastobotrys parvus PPR3 against Pseudomonas aeruginosa PAO1. (January 2020) - Parasuraman, Paramanantham; Devadatha, B.; Sarma, V. Venkateswara; Ranganathan, Sampathkumar; Ampasala, Dinakara Rao; Siddhardha, Busi
Abstract: The bacterial cell communication also termed as Quorum sensing (QS) system was involved in the expression of several virulence traits during Pseudomonas infection. The attenuating of this bacterial cell communication system is an attractive approach for the management of bacterial infections without the complication of resistance development. In this respect, the marine environment has gained significant attention due to its biodiversity and as a source of novel bioactive compounds. The present study aimed to screening effective QS inhibitors from marine associated fungal species for QS inhibitors. Twelve morphologically distinct fungal isolates were isolated from the wood of Avicennia marina from marine ecosystem. The anti-QS potential of fungal crude extract from was investigated in biosensor strain and test bacterium, Chromobacterium violaceum and Pseudomonas aeruginosa PAO1, respectively. Promising anti-QS activity was observed in the crude extract of one of the fungal isolate and identified by molecular characterization using internal transcribed spacer (ITS) region as Blastobotrys parvus PPR3. The anti-virulence and antibiofilm effects of ethyl acetate fractions from PPR3 against P. aeruginosa PAO1 were evaluated. The fungal metabolites responsible for the anti-QS activity of fungal crude extract was identified using gas chromatography-mass spectrometry (GC-MS). Furthermore, molecular docking studies were performed to understand the interaction of bioactive compounds with as receptors of P. aeruginosa PAO1. The crude extract of PPR3 showed reduction in different virulence traits of P. aeruginosa PAO1 such as production of pyocyanin, elastase, protease, chitinase, swimming and swarming motility, biofilm formation, exopolysaccharide production and alginate production at different sub-MIC concentrations. Interaction of bioactive metabolites with LasR and RhlR receptors of P. aeruginosa PAO1 was reported. The findings of the present study suggested that metabolites of B. parvus PPR3 interfere with QS system of P. aeruginosa PAO1 and alters the production of virulence factors. Highlights: Screening and isolating the marine derived fungal isolate with potential antipathogenic activity. Anti-quorum sensing potential of fungal metabolites investigated against P. aeruginosa virulence and biofilm formation. Determining the presence of bioactive compounds in the fungal crude extracts. In silico studies to understand the mechanism of interaction between the QS receptor protein and the ligands.